Role of the Sports Tourism Event Tour de Borobudur for Host City in Government’s Perspective - Ayu Tri Agustin; Soedjatmiko; Tandiyo Rahayu; Dewangga Yudhistira (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Tour de Borobudur is a cycling sport tourism activity held in Central Java. This study aims to analyze the role of organizing the Tour de Borobudur for the Host City from the government’s perspective, both in terms of economic growth and social legacy. The research method used is descriptive quantitative, using an analytical approach and collecting questionnaire data and interviews with ten respondents from relevant government stakeholders. 90.19% (n=3.6) of informants responded positively, meaning the government regarded an economic increase from organizing the Tour de Borobudur. Promoting local potential, increasing micro, small, and medium enterprises (MSMEs), and rising regional retribution revenue have multiplier effects on the economic sector. Also, 90% (n=3.6) of informants responded positively that these activities can influence social legacies, such as increasing interest in cycling sports and improving communication skills, hospitality & tourist management, and increasing the human side of the community. The government plays a role as a facilitator by providing venues, providing budgets, providing security personnel, and becoming participants or just supporters of Tour de Borobudur. The government considers organizing this competition as a medium for developing sports tourism and increasing regional income through sports tourism.